The Educators Personality Development in Industry 4.0 Based on Pumping HR-Model - Amir Tengku Ramly; Renea Shinta Aminda (Integrated Journal of Business and Economics (IJBE), 2020)
Characteristics of Human personality that have existed since birth can be used as a basis for personal development and professionalism at work. Industrial Era 4.0 demands change in all fields, including the world of teaching. This study uses the literature review method by looking for various references critically to obtain valid and reliable data. The results of the analysis found that for the effectiveness of teaching in the classroom, educators must master and understand learning based on students' personalities and themselves. An understanding of the Personality Based Pumping-HR model can describe and map human personality in certain behaviours and characters. The results have a positive impact on the teaching process and teaching outcomes. Changes in the Personality of educators entering the digital era are very important when linked to the success of the teaching is carried out. So for effectiveness in teaching in the 4.0 era, an educator must understand the personality of students.